1993
DOI: 10.1002/ajim.4700230603
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy after occupational exposure to 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin (TCDD)

Abstract: Reports of human exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) describe signs and symptoms consistent with exposure-related peripheral neuropathy. In a cross-sectional study, prevalence of peripheral neuropathy was measured in 265 workers exposed 15 years earlier to chemicals contaminated with TCDD and in 244 unexposed, age-, race-, gender- and community-matched comparisons. Cases of peripheral neuropathy were defined from examination, electrophysiologic and quantitative sensory tests, and symptoms. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The prevalence of peripheral neuropathy among Seveso residents with chloracne or elevated liver function tests suggestive of high exposure was 2.8-fold higher (95% CI 1.2-6.5) than in Seveso residents without such evidence of exposure. Studies of peripheral neuropathy much longer after exposure in Seveso do not support an association, nor is there evidence that dioxin causes a chronic neuropathy in heavily exposed workers (111).…”
Section: Data On Human Health Effectsmentioning
confidence: 94%
“…The prevalence of peripheral neuropathy among Seveso residents with chloracne or elevated liver function tests suggestive of high exposure was 2.8-fold higher (95% CI 1.2-6.5) than in Seveso residents without such evidence of exposure. Studies of peripheral neuropathy much longer after exposure in Seveso do not support an association, nor is there evidence that dioxin causes a chronic neuropathy in heavily exposed workers (111).…”
Section: Data On Human Health Effectsmentioning
confidence: 94%
“…Data set 1 was from a study among newspaper workers [Bernard et al, 1993]; data set 2 from a study of checkers and other workers in four supermarkets [Baron et al, 1991]; data set 3 from a study among operators in a telephone company [Hales et al, 1992]; data set 4 from a study of men poisoned by organophosphate pesticides [Steenland et al, 1994]; and data set 5 from a study of workers exposed to tetrachlorodibenzo-p-dioxin (TCDD) [Sweeney et al, 1993].…”
Section: Methodsmentioning
confidence: 99%
“…Vibrotactile threshold has been used in epidemiologic studies to indicate the presence of neuropathy resulting from exposure to neurotoxic chemicals [Sweeney et al, 1993;McConnell et al, 1994;Steenland et al, 1994]. There has also been interest in its use in the early diagnosis of compression neuropathies such as carpal tunnel syndrome [Lundborg et al, 1986], although the prospects have become less promising with later studies [Werner et al, 1994;Gerr et al, 1995].…”
Section: Introductionmentioning
confidence: 98%
“…The battery of electrophysiologic measures in the present study was selected because of its demonstrated reliability, validity, and sensitivity to compound-induced changes in neural function (Arezzo, Simpson et al 1985;Boyes et al 2009;Herr et al 2007;Spencer 2000). Sensory evoked potentials and peripheral nerve conduction studies have been used by the authors of the present study over the past three decades to demonstrated significant changes in CNS and PNS function associated with a variety of neurotoxic insults (Arezzo et al 1980;Arezzo et al 1982;Arezzo, Schaumburg et al, 1985;Kingman et al 2005;Michalek et al 2001;Pettersen et al 2008;Schaumburg et al 1989;Sweeney et al 1993); exposure to chemotherapy agents and antiviral compounds (Anderson et al, 1994;Reser et al 1999;Swain and Arezzo 2008;Warner 1995); induced inflammation (Brosnan et al 1989;Martiney et al 1990); induced vacuolation Schroeder et al 1992), demyelination (Arezzo et al 1988;Giesser et al 1987), vascular compromise (Horner et al 2004;Portenoy et al 1985); and genetic manipulations (Maycox et al 1997;Michaelson et al 1996). Specifically, the SEP and VEP latency measures reflect transmission within the heavily myelinated afferent fiber tracks of the CNS, including the dorsal columns of the spinal cord, the lemniscal pathways, the optic tracts, and the thalamocortical radiations.…”
Section: Discussionmentioning
confidence: 99%